2015
DOI: 10.3390/rs70911295
|View full text |Cite
|
Sign up to set email alerts
|

Structural Classification of Marshes with Polarimetric SAR Highlighting the Temporal Mapping of Marshes Exposed to Oil

Abstract: Abstract:Empirical relationships between field-derived Leaf Area Index (LAI) and Leaf Angle Distribution (LAD) and polarimetric synthetic aperture radar (PolSAR) based biophysical indicators were created and applied to map S. alterniflora marsh canopy structure. PolSAR and field data were collected near concurrently in the summers of 2010, 2011, and 2012 in coastal marshes, and PolSAR data alone were acquired in 2009. Regression analyses showed that LAI correspondence with the PolSAR biophysical indicator vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The Landsat data show significant oiling effects on the mashes in 2010 and 2011, the year of and the year after the Deepwater Horizon oil spill, which is consistent with results from the AVIRIS data, the PolSAR data [34,35], and field observations [9]. The comparison between the heavily oiled site and the non-oiled site performed in this study is based on the greatest contrast in oiling conditions, and thus, represents the worst scenario of oiling damage on the marshes.…”
Section: Impact Of Oil Exposure On the Marsh Vegetationsupporting
confidence: 72%
“…The Landsat data show significant oiling effects on the mashes in 2010 and 2011, the year of and the year after the Deepwater Horizon oil spill, which is consistent with results from the AVIRIS data, the PolSAR data [34,35], and field observations [9]. The comparison between the heavily oiled site and the non-oiled site performed in this study is based on the greatest contrast in oiling conditions, and thus, represents the worst scenario of oiling damage on the marshes.…”
Section: Impact Of Oil Exposure On the Marsh Vegetationsupporting
confidence: 72%
“…C-band SAR (5.56-cm wavelength) is particularly suitable for separating/identifying emergent marsh vegetation based on biomass. Ramsey et al and Dabrowska-Zielinska et al both demonstrated strong statistical relationships between leaf area index (LAI) and cross-polarized C-band backscatter in emergent marsh wetlands [30,31]. With an increasing biomass of shrubs and trees, C-band signals saturate, limiting their ability to differentiate high biomass emergent marsh vegetation from forest-and shrub-dominated wetlands [32].…”
mentioning
confidence: 99%
“…For many years, satellite SAR was considered to be a tool for detecting oil in open ocean environments [14,15]; oil in nearshore marsh habitats was evaluated mostly from the ground or low-flying aircraft [2,3,16] or from aerial SAR platforms such as UAVSAR [8,11]. However, during DWH, oil was detectable in satellite SAR imagery in Louisiana nearshore areas, including areas with marsh habitats, on the vast majority of days during the DWH spill.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that scaling their observations to a coarser satellite-based spatial sensor (Landsat Enhanced Thematic Mapper Plus, or ETM+) greatly reduced the detection of oil spectral signatures. After the DWH spill, Ramsey et al [11] carried out a multiyear monitoring study using the aerial UAVSAR sensor over the marsh sites affected by the DWH on the Barataria Bay. This study demonstrated the utility of radar-based oil detection in marsh habitats, but the data collection included the logistical challenge and expense of mobilization aircraft.…”
Section: Introductionmentioning
confidence: 99%